Comparison of lignin degradation and flavor compound formation in roasted tobacco by two Bacillus subtilis strains - Wang, Junmin; Long, Teng; Jiang, Zhenkun; Mu, Wenjun; Su, Mingliang; Ni, Li; Ji, Shunhua; Wang, Yuqing; Zhou, Kangxi; Zhan, Renfeng; Nie, Lixuan; Li, Jingjing; et al. (Frontiers in Microbiology, 2025)
Two strains of Bacillus subtilis designated YY-10 and BY-2, were isolated from the surface of tobacco and found to be capable of significant lignin degradation. The predominant lignin-degrading enzymes produced by these strains were lignin peroxidase (LiP) and manganese peroxidase (MnP), respectively. A notable distinction was observed in the organoleptic evaluation and volatile flavor compounds, as determined by sensory evaluation and GC–MS analysis. The content of volatile flavor compounds, such as geranylacetone, meglumine trienone B, and meglumine trienone C, was found to be significantly increased in roasted tobacco treated with YY-10. This treatment has been shown to reduce the astringent flavor of the roasted tobacco and improve the aroma, which in turn could improve the quality of the roasted tobacco. Conversely, the quality and aroma levels of the roasted tobacco treated with the crude enzyme solution of the BY-2 strain were reduced. Transcriptome analysis revealed that the expression of genes related to amino acid metabolism, genetic material biosynthesis, and protein synthesis was up-regulated in the YY-10 strain compared with the BY-2 strain, which promoted the biosynthesis of LiP. This study provides a preliminary elucidation of the potential mechanism by which YY-10 enhances the quality of tobacco leaves through lignin-degrading enzyme production, thus establishing a research foundation for the subsequent treatment of waste tobacco raw materials and industrial applications.